2016
DOI: 10.1016/j.gca.2016.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Structural response of phyllomanganates to wet aging and aqueous Mn(II)

Abstract: 41 Naturally occurring Mn(IV/III) oxides are often formed through microbial Mn(II) 42 oxidation, resulting in reactive phyllomanganates with varying Mn(IV), Mn(III), and vacancy 43 contents. Residual aqueous Mn(II) may adsorb in the interlayer of phyllomanganates above 44 vacancies in their octahedral sheets. The potential for interlayer Mn(II)-layer Mn(IV) 45 comproportionation reactions and subsequent formation of structural Mn(III) suggests that 46 aqueous Mn(II) may cause phyllomanganate structural changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…They commonly occur as fine-grained, poorly crystalline aggregates and coatings, making the studies of their structures and behaviors challenging. Additionally, various synthetic birnessite-like structures containing almost every possible alkali and alkaline earth element, as well as many of the transition metals, have been synthesized (e.g., McKenzie, 1971;Golden et al, 1986) in attempts to elucidate the structural and chemical features of birnessite-like phyllomanganates (e.g., Post and Veblen, 1990;Drits et al, 1997;Silvester et al, 1997;Lanson et al, 2000;Post et al, 2002;Feng et al, 2004;Händel et al, 2013) and their reactivities (e.g., (Manceau et al, 2002;Feng et al, 2007;Lopano et al, 2007Lopano et al, , 2011Landrot et al, 2012;Wang et al, 2010;Kwon et al, 2013;Lefkowitz et al, 2013;Yin et al, 2013;Fischel et al, 2015;Hinkle et al, 2016;Zhao et al, 2016;Fischer et al 2018). Laboratory studies have also demonstrated that formation of birnessite-like phases can be initiated, or enhanced, by certain microbes and This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Birnessite-like Phasesmentioning
confidence: 99%
“…They commonly occur as fine-grained, poorly crystalline aggregates and coatings, making the studies of their structures and behaviors challenging. Additionally, various synthetic birnessite-like structures containing almost every possible alkali and alkaline earth element, as well as many of the transition metals, have been synthesized (e.g., McKenzie, 1971;Golden et al, 1986) in attempts to elucidate the structural and chemical features of birnessite-like phyllomanganates (e.g., Post and Veblen, 1990;Drits et al, 1997;Silvester et al, 1997;Lanson et al, 2000;Post et al, 2002;Feng et al, 2004;Händel et al, 2013) and their reactivities (e.g., (Manceau et al, 2002;Feng et al, 2007;Lopano et al, 2007Lopano et al, , 2011Landrot et al, 2012;Wang et al, 2010;Kwon et al, 2013;Lefkowitz et al, 2013;Yin et al, 2013;Fischel et al, 2015;Hinkle et al, 2016;Zhao et al, 2016;Fischer et al 2018). Laboratory studies have also demonstrated that formation of birnessite-like phases can be initiated, or enhanced, by certain microbes and This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Birnessite-like Phasesmentioning
confidence: 99%
“…The ability of microbes to reduce freshly precipitated MnO x(s) when coupled with the oxidation of various organic compounds has been reported by a wide variety of authors, with one of the seminal papers being published by Lovley and Phillips (1988). Aging has been shown to produce chemical and structural changes in the forms of MnO x(s) present (Cui et al., 2010; Hinkle et al., 2016). Likewise, variations in MnO x(s) crystalline structure affect Mn reactivity (Stone, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…The dissolved Mn(II) and the structural Mn(III/II) could further modify the fine structures of Mn oxides, or even promote the inter-transformation among different mineral phases (Lefkowitz et al , 2013; Hinkle et al , 2016). For birnessite especially, the vacancy abundance, layer stacking, in-plane crystallinity within the phyllomanganate sheets and local coordination structure centring the Mn atoms will all be likely to alter (Wang et al , 2018; Flynn and Catalano, 2019).…”
Section: Environmental Functions Of Mn Oxides Controlled By Mn Redox mentioning
confidence: 99%
“…Notably, these structural responses after the redox reaction with organics are also liable to be affected by pH conditions. In a weakly acid environment of pH 4–6, Mn(III/II) tends to migrate into the inter-layer space and adsorb in the layer above vacancies (Wang et al , 2018; Flynn and Catalano, 2019), which will strengthen the layer stacking (Marafatto et al , 2015; Flynn and Catalano, 2019); in contrast, some of the Mn(III) also appears to locate at the layer edge sites, which, together with the abundant presence of dissolved Mn(II) in acidic solutions, might help induce the re-ordering of layer sheets towards triclinic symmetry (Hinkle et al , 2016; Flynn and Catalano, 2019). Under neutral to alkaline solutions, the generated Mn(III) is more likely to be incorporated into vacant sites and reside in the layer (Wang et al , 2018); further, with the effect of Mn(II), additional mineral phases may form, such as manganite, feitknechtite and hausmannite (Lefkowitz et al , 2013; Wang et al , 2018; Zhang et al , 2018).…”
Section: Environmental Functions Of Mn Oxides Controlled By Mn Redox mentioning
confidence: 99%